Navigating Diversity Through Homogeneity: A Comparative Study of Multicultural Value Implementation in Islamic and Christian Education at an Indonesian Junior High School - Irma Sulistia Silaen; Salminawati Salminawati; Zaini Dahlan (Journal of Social Work and Science Education, 2026)
This study aims to analyze the implementation of multicultural values ​​in Islamic Religious Education and Christian Religious Education learning at SMP Negeri 2, Kualuh Selatan District. This study uses a qualitative approach with a descriptive case study method to gain a deep understanding of how multicultural values ​​are integrated into religious learning in a school environment with diverse religious backgrounds. Data collection techniques were carried out through observation, in-depth interviews with the principal, Islamic Religious Education teachers, Christian Religious Education teachers, and students, and supported by documentation studies. Data analysis used the interactive analysis model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing, while data validity was guaranteed through source triangulation and method triangulation. The results of the study indicate that religious teachers at SMP Negeri 2, Kualuh Selatan District have a good understanding of multicultural values ​​based on their respective theological perspectives. Islamic Religious Education teachers understand multicultural values ​​as a form of tolerance based on the teachings of the Qur’an and Islamic values, while Christian Religious Education teachers emphasize the value of universal love in Christian teachings as the basis for respect for fellow human beings. The implementation of multicultural values ​​in religious education is carried out through various strategies, such as collaborative learning, interactive discussions, the use of diverse learning media, religious literacy programs, and worship practices that emphasize mutual respect among students of different religions. This study concludes that religious education can be a strategic tool for instilling multicultural values ​​and strengthening tolerance among students in a pluralistic school environment.